Model Kepemimpinan Digital untuk Multipikasi Pemimpin Muda - Fransiscus Fransiscus; Gabby Naca Stevany; Priscilla Paay; Yeghar Galed Laransedu; Manlian Ronald A. Simanjuntak (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The challenges of leaders continue to grow with the presence of digital technology in the development of the era of technological transformation, in addition to being a digital challenge, this also becomes a new opportunity for leaders. Digital transformation plays an important role in realizing leadership. A leader can be called a digital leader if a leader is able to lead and utilize technology. The purpose of this study is to show the best digital leadership model in realizing leadership multiplication in the younger generation. Qualitative research methods with a literature study approach are used in this study. The results of the study show that the role of digital transformation plays a very important role in building the multiplication of young leaders. Information technology can be utilized as a work process in all sectors, especially the religious sector. In addition, leaders will find it easier to make decisions on the use of data.